Canadian Rockies 2026 : [with Banff & Jasper National Parks : scenic drives, wildlife, hiking & skiing] - Hempstead, Andrew (Moon travel handbooks., 2025)
"Snowy peaks, icy glaciers, glittering lakes, and alpine Answer the call of the wild with Moon Canadian Rockies. Inside you'll Strategic, flexible itineraries in the national parks, including a two-week Canadian Rockies road tripThe best hikes in the Canadian Find the right trek for you with details on length, elevation gains, difficulty levels, and trailheads Can't-miss outdoor Hike to incredible vistas and try to spot moose, bighorn sheep, wolves, and black bears. Soak in a natural hot spring after a day on the slopes or wander through meadows of colorful wildflowers. Ride across the Columbia Icefield in an Ice Explorer, float through the sky in a mountain gondola, or white-water raft down rivers of snowmelt. Go horseback riding though the Tonquin Valley or fish for your own fresh dinner and camp under the stars Expert insight from Banff local Andrew Hempstead on when to go, where to eat, and where to stay, from campgrounds to luxurious mountain lodges Full-color photos, detailed maps of each park, and handy directions, including driving times and mileages, and coverage of gateway towns Background information on the landscape, culture, history, wildlife, and environment In-depth coverage of Banff National Park, Kootenay National Park, Yoho National Park, Jasper National Park, Waterton Lakes National Park, and nearby cities of Banff, Canmore, Jasper, Calgary, Radium Hot Springs, Golden, and Kananaskis Country With Moon's practical tips and local insight, you can experience the best of the Canadian Rockies. Hitting the road? Try Moon U.S. and Canadian Rockies Road Trip. Focusing on the parks? Check out Moon Best of Glacier, Banff, and Jasper. About Moon Travel Moon was founded in 1973 to empower independent, active, and conscious travel. We prioritize local businesses, outdoor recreation, and traveling strategically and sustainably. Moon Travel Guides are written by local, expert authors with great stories to tell-and they can't wait to share their favorite places with you."--Goodreads.